2021
DOI: 10.1186/s40359-021-00677-5
|View full text |Cite
|
Sign up to set email alerts
|

The association of parental involvement with adolescents’ well-being in Oman: evidence from the 2015 Global School Health Survey

Abstract: Background The parent-adolescent relationship plays a key role in adolescent development, including behaviour, physical health, and mental health outcomes. Studies on the parental factors that contribute to an adolescent’s dietary habits, exercise, mental health, physical harm and substance use are limited in the Middle East and North Africa region, with none in Oman. This study aims to investigate the association between parental involvement and adolescent well-being in Oman. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As shown in Table 2, better relationships have the most important impact on mental health of children, and this is in agreement with studies that show a meaningful relationship with family members bridge individuals to wider social resources. Also other important factors such as parental monitoring and family structure could affect the mental health of children and adolescents and further investigations should be conducted in order to examine the relationship of family structure and parenting to social capital (29,30). The idea of family structure impact on development of psychiatric disorders in children and adolescent could be inferred from our results which indicate that better relationship, cooperation, mutual understanding and commitment have significant effect on their mental health.…”
Section: Discussionmentioning
confidence: 78%
“…As shown in Table 2, better relationships have the most important impact on mental health of children, and this is in agreement with studies that show a meaningful relationship with family members bridge individuals to wider social resources. Also other important factors such as parental monitoring and family structure could affect the mental health of children and adolescents and further investigations should be conducted in order to examine the relationship of family structure and parenting to social capital (29,30). The idea of family structure impact on development of psychiatric disorders in children and adolescent could be inferred from our results which indicate that better relationship, cooperation, mutual understanding and commitment have significant effect on their mental health.…”
Section: Discussionmentioning
confidence: 78%
“…However, parental involvement in the adolescent’s life has been identified as a protective factor from being harassed by many researchers [ 29 , 33 ]. Recent studies using GSHS in Oman and Vietnam identified parental involvement as a protective factor from bullying victimization [ 45 , 46 ]. This might be explained by a healthy parent–child relationship, allowing a protective environment against the peer pressure influences [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using GSHS in Oman and Vietnam identified parental involvement as a protective factor from bullying victimization [ 45 , 46 ]. This might be explained by a healthy parent–child relationship, allowing a protective environment against the peer pressure influences [ 45 , 47 ]. Indeed, modern trends highlighted adolescent’s needs for independence, but parental support plays a key role in guiding children to the next level of social skills and promoting their mental health [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A topic for future research, this may ultimately be explained by paternal frustration, self-criticism, and rage, manifesting as violent, abusive, or neglectful child maltreatment. Because societal conventions create expectations that fathers will work outside the home, these outcomes occur more frequently in homes with an unemployed father than in those with an unemployed mother, resulting in child maladjustment [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%